Ethnicity, religion and clinical practice: a qualitative study of beliefs and attitudes of psychiatrists in the United Kingdom - Durà-Vilà, Glòria (Mental health, religion & culture, 2011)
There is growing interest in the relationship between religion and mental health and the need for compassion, empathy and "spiritual competencies" within health services including psychiatry. The nature and the extent of such a relationship are highly vexed and polarising within the psychiatric profession. While the United Kingdom is ostensibly a secular society, a high percentage of NHS clinicians hail from religiously oriented societies; we know little on how the religious beliefs of such professionals are resolved in a secular practice. This is a qualitative study exploring psychiatrists’ attitudes to religion and spirituality within their practice and which attempts to examine how these are resolved in the therapeutic relationship with, and management of, religious patients. Twenty interviews were conducted with psychiatrists working in London. The main finding was the strong degree of dissonance amongst the migrant psychiatrists between their practice in their home countries (incorporating patients’ religious beliefs) and in the United Kingdom (excluding them). The need for more training in this area and the relevance of the results are discussed and placed in the context of previous literature.